EXISTENCE OF WITNESSES IN MARRIAGE ACCORDING TO HADIST PERSPECTIVE - Rahmawati, Rahmawati; Elihami, Elihami (Al-Mirah: Jurnal Pendidikan Islam, 2019)
A marriage contract is analogous to a sale and purchase agreement, then women are free or have the right to make a marriage contract, as women are free and have the right to enter into a contract of sale and purchase. Thus, women have the free right to make a marriage contract because there is no legal difference between contracts. In a marriage contract, although guardians have rights, they are not absolute. Guardians can only exercise their absolute trust rights if there is an error made by the woman in doing so or marrying an unequal male. It is said so because of the mistake of women in making a marriage contract, will also cause disgrace on his guardian in the future.